Modeling the depletion and reconstitution of W ': Effects of prior exercise on cycling tolerance - Nascimento Salvador, Paulo Cesar do; Lucas, Ricardo Dantas de; Schafer, Lisa; Antonacci Guglielmo, Luiz Guilherme; Grassi, Bruno; Denadai, Benedito Sergio [UNESP] (Elsevier B.V., 2021)
Thirteen healthy male subjects (age 28 +/- 7 years) performed tests for critical power and W' determination and two square-wave high-intensity exercises until exhaustion either with prior very-heavy intensity cycling (EXP) or without (CON). Prior exercise bout induced a depletion of 60 % of W'. After 10 min of recovery, W' reconstitution was not fully achieved (similar to 92 %). Time to exhaustion and Delta blood lactate concentration were significantly lower in EXP compared to CON (595 +/- 118 s vs. 683 +/- 148 s; 3.5 +/- 1.2 mmol.L-1 vs. 8.8 +/- 2.3 mmol.L-1 ; p < 0.05, respectively). Oxygen uptake (VO2) and heart rate were significantly higher in EXP, during the first 150 s of exercise (p < 0.05). The carbon dioxide production kinetics was significantly slower in EXP (mean response time = 87.8 +/- 17.8 s vs. 73.7 +/- 16.6 s in CON; p < 0.05). Thus, prior exercise impairs high-intensity cycling performance which can partly be explained by physiological disturbances linked to W' depletion.
Keywords: W ' reconstitution; W ' balance; VO2 dynamic; Exhaustion; Very-heavy intensity domain; Cycling tolerance